DIASPORA AND MIGRATION POLICY - State Planning Board, Government of Kerala
Due to migration, there is increase in remittances which increase consumption, economic growth as well as have had some salutary effects on the current account balance. However, it constrain the long term growth prospects by creating a resource-curse like situation (Dutch disease) in Kerala. And it has also been observed that remittances reduce the work incentive and entrepreneurship of recipients of remittances in the home economy. In case of permanent emigration, Kerala loses direct benefits from the skills and work of an emigrant forever. Vulnerability of the migrants coming from other part of countries arises due to differences in language, culture, legal protection, social setting and loss of the support system that they have in their native place. The proposed strategy is to mainstream the three categories of migrants: NRKs, return emigrants, and in-migrants, in the development agenda by creating an enabling environment into which the migrants are effectively integrated and able to make significant contribution to the development of the country. The main thrust is therefore, to harness the diaspora (including return migrants) and in-migrants as a resource for development .